2017
DOI: 10.1016/j.hrthm.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac phenotype and long-term prognosis of arrhythmogenic right ventricular cardiomyopathy/dysplasia patients with late presentation

Abstract: One-fifth of all ARVC/D patients present after age 50 years, often with sustained ventricular tachycardia, and are less likely to have prior syncope, ECG changes, ventricular ectopy, or identifiable pathogenic mutation. In ARVC/D, late presentation does not confer a benign prognosis and is associated with high arrhythmic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 33 publications
0
31
1
Order By: Relevance
“…64 Whereas adult patients more often present with sustained VT, paediatric patients are more likely to experience SCD or resuscitated sudden cardiac arrest. 45,63,65 Sudden cardiac death may be the first clinical manifestation of the disease, as it was reported by a study in the Veneto region of Italy, where 20% of SCD in young people and athletes were caused by previously undiagnosed ARVC. 66 The diagnosis of ARVC is particularly challenging in children <14 years of age.…”
Section: Diagnosis Of Arrhythmogenic Right Ventricular Cardiomyopathymentioning
confidence: 89%
“…64 Whereas adult patients more often present with sustained VT, paediatric patients are more likely to experience SCD or resuscitated sudden cardiac arrest. 45,63,65 Sudden cardiac death may be the first clinical manifestation of the disease, as it was reported by a study in the Veneto region of Italy, where 20% of SCD in young people and athletes were caused by previously undiagnosed ARVC. 66 The diagnosis of ARVC is particularly challenging in children <14 years of age.…”
Section: Diagnosis Of Arrhythmogenic Right Ventricular Cardiomyopathymentioning
confidence: 89%
“…It is rare for patients with ARVC to have clinical signs or symptoms of ARVC prior to 12 years of age. It is also uncommon to first develop signs or symptoms of ARVC after the age of 60 years 10, 14, 16 . Symptoms are largely due to the presence of ventricular arrhythmias.…”
Section: Arvcmentioning
confidence: 99%
“…Bhonsale et al demonstrated that AC patients experiencing VF and SCD were significantly younger (median age 23 years) than those presenting with sustained monomorphic VTs (median age 36 years) [47]. A subsequent study by the same group showed that in patients with late presentation (>50 years) sustained VT was the predominant arrhythmic event, in contrast to the young people, in whom VF was more common [48]. A pathobiological explanation of this particular age-related arrhythmic behavior may be due to the progressive nature of the disease, which modifies the myocardial lesions over time.…”
Section: Age-related Arrhythmic Manifestationsmentioning
confidence: 99%
“…Interesting age-related differences in arrhythmic manifestations have been observed and should be taken in mind while evaluating AC patients [44,47,48]. Cardiac arrest by ventricular fibrillation (VF) is mostly reported during the earlier phases of AC, whereas sustained VTs occur more commonly later in the disease course.…”
Section: Age-related Arrhythmic Manifestationsmentioning
confidence: 99%